The Developement of Education and Training Model in the Preparation of Cooperative Financial Reports Based on Sak-Etap in Pekalongan City - Suherlina, Lina; Suryatna, Bambang Sugeng; Endroyo, Bambang (Journal of Vocational and Career Education, 2019)
Finance Entity of Accounting Standardization without Public Accountability (SAK-ETAP) is one of finance accounting standardize which become a manual in reporting finance for entity that do not have public accountability for external users. The purpose of this research is to examine the validity and the effectiveness of education and training model in constructing of Cooperative finance report at Pekalongan. This research uses quantitative research methodology. The informants come from Industrial Affairs, Economic Enterprise/ Cooperatives and small business (UKM) Pekalongan, Cooperatives Management and public accountant. The data collection technique uses observation, interview, documentation and design guiding. This research uses T-test validity to examine the data. Before reporting finance design based on Finance Entity of Accounting Standardization without Public Accountability is used, it will be validated by the expert. The research finding show that education and training model is effective. Based on research finding in pilot study the knowledge and the skill of participants of the research increase tremendously. It is got from the gap between pretest and posttest in T-test validity. Therefore collaboration between Cooperative and related organization can help in reporting finance report according to applicable standards.